EFFICACY OF SELECTIVE ALPHA-1 RECEPTOR BLOCKERS (TAMSULOSIN) IN FACILITATING THE PASSAGE OF RENAL STONES AFTER EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY - Nauman Khalid; Aijaz Hussain Memon; Wasim Sarwar Bhatti; Hanan Noor; Muhammad Waqas Iqbal; Muhammad Sohail (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Urinary system stone disease is a common entity. Small renal stones are preferably treated using Extracarporeal Shock Wave Lithotripsy (ESWL) technique. Passage of stone fragments result in pain, hematuria and urinary tract obstruction. This can be avoided by the use selective α-1 receptor antagonists like Tamsulosin. However, their efficacy remains a matter of debate. In this study the role of selective α-1 blocker was evaluated in facilitating spontaneous expulsion of renal stone fragments after ESWL. The objective of our study was to find out the Efficacy of Tamsulosin (Selective α-1 blocker) in facilitating the transit of stone fragments (4-7mm) after ESWL. Follow up X-ray KUB was used to confirm the stone clearance. Efficacy was measured in terms of stone expulsion rate. METHODOLOGY: It was randomized controlled trial including 150 patients coming to outpatient department of Urology Lahore General Hospital, Lahore from January 25, 2010 to July 25, 2010. Total 150 patients with renal stones broken down into fragments (4-7mm) after ESWL were enrolled using non-probability purposive sampling technique. Patients were categorized into group A and B. Patients of group A received cap. Tamsulosin 0.4mg along with Tab. Diclofenac sodium 50mg. Whereas, patients belonging to group B received only diclofenac sodium 50 mg twice daily. Patients underwent ESWL every three weeks, in case of non-fragmentation, to the maximum of 4 sessions. All the patients were followed with X Ray KUB for stone clearance. The data of all patients was incorporated into pre designed Performa. Statistical evaluation of clinical variables done in terms of efficacy i.e. stone clearance. RESULTS: Stone clearance rate of patients in group A was 86.6% as compared to only 76% in group B. Usage of selective α-1 blockers in group A enhanced the stone clearance rate as compared to group B. However this difference was statistically insignificant (p-value-0.094). CONCLUSION: There was increased stone clearance in alpha one blocker group but not statistically significant. Further studies with larger sample size are required to evaluate the role of Selective α-1 blockers (Tamsulosin) after ESWL.